Silicon-carbon negative electrode material with high mechanical strength
By using extrusion granulation and carbon coating treatment technology in silicon carbon negative electrode materials and combined with PVDF composite, the problem of insufficient density of porous silicon carbon negative electrode materials is solved, which significantly improves the mechanical strength and electrochemical performance of the material, and meets the satisfaction of Energy density requirements for lithium-ion batteries.
Patent Information
- Application Number
- CN202411257052.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-13
AI Technical Summary
The existing porous silicon carbon negative electrode materials have low loose density and compaction density, which is not conducive to the preparation of high surface load battery electrode sheets and limits the energy density of the battery.
By dispersing nanosilicon, carbon source, LiBF4 and lithium carbonate in the solvent and stirring evenly, extrusion and granulation and two calcining, then carbon coating was carried out by chemical vapor deposition, and heat treatment was combined with PVDF to adjust the material Mechanical strength and electrochemical properties.
It improves the mechanical strength and electrochemical properties of the material, enhances the cycle stability and energy density of the battery, and meets the needs of commercial lithium-ion batteries.
Smart Images

Figure BDA0005034409750000081 
Figure BDA0005034409750000091
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of silicon-carbon negative electrode materials, and in particular to a silicon-carbon negative electrode material with high mechanical strength. Background Art
[0002] Silicon materials have an ultra-high theoretical specific capacity (Li 22 Si5, 4200mAh / g), abundant reserves and low cost have become the focus and hotspot of current research and development of lithium-ion battery electrode materials. However, silicon materials are accompanied by huge volume expansion (up to 300%) during the charging and discharging process, which can easily cause silicon particles to break or pulverize, electrical contact failure, and rapid decline in battery performance, which seriously restricts the industrialization of silicon negative electrode materials. In order to inhibit and alleviate the volume expansion of silicon negative electrodes, improvements are mainly made by nano-sizing silicon and constructing silicon-carbon composite materials with loose and porous structures and good particle dispersion. In silicon-carbon composite materials, carbon materials can inhibit the agglomeration of nano-silicon and buffer the volume expansion of silicon; at the same time, the good electrical conductivity of carbon materials can effectively improve the electrical contact after the volume expansion of silicon, thereby effectively improving the electrochemical performance of the material. However, the current porous silicon-carbon negative electrode materials have low bulk density and compaction density, which is not conducive to obtaining battery pole pieces with high surface loading. In addition, when the pole pieces are rolled in the later stage, the porous structure is very easy to be damaged, the specific surface area is positively increased, and the electrochemical performance is seriously attenuated, which is difficult to meet the needs of commercial lithium-ion battery applications. Therefore, there is an urgent need to develop silicon-carbon negative electrode materials with high mechanical strength. Summary of the invention
[0003] The purpose of this application is to provide a silicon-carbon negative electrode material with high mechanical strength, so as to solve the technical problem that the porous silicon-carbon negative electrode material in the prior art has low loose density and compacted density, which is not conducive to the preparation of high-area-load battery pole pieces and limits the energy density of the battery.
[0004] The present application provides a silicon-carbon negative electrode material with high mechanical strength, comprising the following preparation steps:
[0005] Step 1, dispersing nano-silicon, carbon source, LiBF4 and lithium carbonate in a solvent, and stirring to obtain a suspension;
[0006] Step 2, the suspension obtained in step 1 is treated by extrusion granulation to obtain a sample after pressurized granulation, and the inlet temperature of the extruder is controlled to be 150° C. and the outlet temperature is controlled to be 80° C.;
[0007] Step 3, calcining the pressurized granulated sample obtained in step 2 twice under an inert atmosphere to obtain a silicon-carbon negative electrode precursor material;
[0008] Step 4, subjecting the silicon-carbon negative electrode precursor material obtained in step 3 to carbon coating by chemical vapor deposition to obtain a carbon-coated negative electrode material;
[0009] Step 5: Compound the carbon-coated negative electrode material obtained in step 4 with PVDF in a mass ratio of 9.9:0.1, and perform heat treatment at 750° C. to obtain the desired silicon-carbon negative electrode material.
[0010] Preferably, in step 1, the mass ratio of nano-silicon: carbon source: LiBF4: lithium carbonate is 40:40:10:10.
[0011] Preferably, in step 3, the first calcination temperature is 850°C, the heating rate is controlled at 5°C / min, and the holding time is 2 hours; the second calcination temperature is 1100°C, the heating rate is controlled at 5°C / min, and the holding time is 2 hours.
[0012] Preferably, in step 1, nano-silicon, carbon source, LiBF4 and lithium carbonate are dispersed in a solvent and then stirred using a magnetic stirrer for 1-3 hours.
[0013] Preferably, in step 1, the carbon source is one or more of starch, citric acid, phenolic resin, asphalt and polyvinyl pyrrolidone.
[0014] Preferably, in step 1, the solvent is one or more of ethanol and isopropanol.
[0015] Preferably, in step 1, the carbon source further includes one or more of graphite, carbon fiber and graphene oxide.
[0016] Preferably, in step 4, the temperature of carbon coating is 850° C., the gas source used is a mixed gas of acetylene and methane, and the duration is 1 hour.
[0017] Therefore, the present application adopts the above-mentioned silicon-carbon negative electrode material with high mechanical strength, which has the following beneficial effects:
[0018] (1) By adjusting the mixing ratio of nano-silicon, carbon source, LiBF4 and lithium carbonate, the surface oxide layer of the silicon material is consumed, the first coulomb efficiency of the material is improved, and the doping of B and Al elements improves the conductivity of the material and the rate performance is better.
[0019] (2) By extruding and granulating the mixed suspension, the bonding force between nano-silicon and carbon source can be improved, thereby increasing the mechanical strength of the material.
[0020] (3) The first calcination temperature is 850°C, which is conducive to the pyrolysis of the carbon source and the bonding between nano-silicon and the carbon source. The second calcination temperature is 1100°C, which is conducive to further improving the crystallinity and stability of the material.
[0021] (4) The thermal decomposition of composite PVDF is conducive to the release of HF for surface fluorination of the elastic cloud, which is beneficial to the formation of an inorganic LF-rich interface during the cycle of the battery negative electrode material, thereby improving the average coulombic efficiency of the battery and enhancing the cycle stability of the battery. DETAILED DESCRIPTION
[0022] Example 1
[0023] Step 1: Weigh the raw materials according to the mass ratio of nano-silicon: carbon source: LiBF4, lithium carbonate of 40:40:10:10, add the weighed materials into ethanol solvent, and stir with a magnetic stirrer for 3 hours. Ensure that the nano-silicon, starch, LiBF4 and lithium carbonate are fully dispersed in the solvent to avoid agglomeration.
[0024] Step 2: Set the inlet temperature of the extruder to 150° C. and the outlet temperature to 80° C., inject the suspension obtained in step 1 into the extruder, start the extruder, adjust the extrusion speed, and obtain a sample after pressurized granulation.
[0025] Step 3, the pressurized granulated sample obtained in step 2 is calcined twice under an inert atmosphere to obtain a silicon-carbon negative electrode precursor material: after the furnace is preheated, the pressurized granulated sample obtained in step 2 is placed in a furnace and calcined under an inert atmosphere, the calcination temperature is between 850°C, the heating rate is controlled at 5°C / min, and the insulation time is 2 hours, so that the sample undergoes a chemical reaction at high temperature. After the calcination is completed, the sample is taken out of the furnace, and the sample after the first calcination is placed in a high temperature resistant container again, and the container is also ensured to be sealed under an inert atmosphere. The container is placed in a high temperature furnace, and the temperature is raised to 1100°C at 5°C / min, and the insulation time is 2 hours. After the calcination is completed, the high temperature furnace is turned off, and it is naturally cooled to room temperature. The sample is taken out to obtain a silicon-carbon negative electrode precursor material.
[0026] Step 4: using a chemical vapor deposition method, at a temperature of 850° C., using a mixed gas of acetylene and methane to perform a carbon coating treatment on the silicon-carbon negative electrode precursor material obtained in step 3 for 1 hour to obtain a carbon-coated negative electrode material;
[0027] Step 5. After the carbon-coated negative electrode material obtained in step 4 is fully dried, it is mixed with polyvinylidene fluoride PVDF in a mass ratio of 9.9:0.1, and placed in a mixing container for mechanical stirring to make the two mixed evenly, and then the material is pre-pressed. The pre-pressed green body is placed in a heat treatment furnace, heated at a rate of 10°C / min, and heat treated at 750°C. After the heat treatment, the power is turned off, and the heat-treated green body is naturally cooled to room temperature in the furnace, taken out, and the burrs are removed to obtain the desired silicon-carbon negative electrode material.
[0028] Comparative Example 1
[0029] Step 1: Disperse nano-silicon, carbon source, LiBF4 and lithium carbonate in a solvent and stir to obtain a suspension: weigh the raw materials according to the mass ratio of nano-silicon: starch: LiBF4 and lithium carbonate of 40:50:10:10, add the weighed materials into the ethanol solvent, and stir with a magnetic stirrer for 3 hours. Ensure that the nano-silicon, starch, LiBF4 and lithium carbonate are fully dispersed in the solvent to avoid agglomeration.
[0030] Step 2: The suspension obtained in step 1 is treated by extrusion granulation, and the inlet temperature of the extruder is controlled to be 150°C and the outlet temperature is controlled to be 80°C: the inlet temperature of the extruder is set to 150°C, the outlet temperature is set to 80°C, the suspension obtained in step 1 is injected into the extruder, the extruder is turned on, the extrusion speed is adjusted, and the sample after pressurized granulation is obtained.
[0031] Step 3: The pressurized granulated sample obtained in step 2 is calcined twice under an inert atmosphere to obtain a silicon-carbon negative electrode precursor material: After the furnace is preheated, the pressurized granulated sample obtained in step 2 is placed in a furnace and calcined under an inert atmosphere. The calcination temperature is between 850°C, the heating rate is controlled at 5°C / min, and the insulation time is 2 hours, so that the sample undergoes a chemical reaction at high temperature. After the calcination is completed, the sample is taken out of the furnace, and the sample after the first calcination is placed in a high-temperature resistant container again. Similarly, ensure that the container is sealed under an inert atmosphere, and place the container in a high-temperature furnace, and raise the temperature to 1100°C at 5°C / min, and the insulation time is 2 hours. After the calcination is completed, the high-temperature furnace is turned off, and the sample is naturally cooled to room temperature, and the sample is taken out to obtain a silicon-carbon negative electrode precursor material.
[0032] Step 4: Using chemical vapor deposition, at a temperature of 850° C., use a mixed gas of acetylene and methane to perform carbon coating treatment on the silicon-carbon negative electrode precursor material obtained in step 3 for 1 hour to obtain a carbon-coated negative electrode material.
[0033] Step 5. After the carbon-coated negative electrode material obtained in step 4 is fully dried, it is mixed with polyvinylidene fluoride in a mass ratio of 9.9:0.1, and placed in a mixing container for mechanical stirring to make the two mixed evenly, and then the material is pre-pressed. The pre-pressed green body is placed in a heat treatment furnace, heated at a rate of 10°C / min, and heat treated at 750°C. After the heat treatment, the power is turned off, and the heat-treated green body is naturally cooled to room temperature in the furnace, taken out, and the burrs are removed to obtain the desired silicon-carbon negative electrode material.
[0034] Comparative Example 2
[0035] Step 1: Disperse nano-silicon, carbon source, LiBF4 and lithium carbonate in a solvent and stir to obtain a suspension: weigh the raw materials according to the mass ratio of nano-silicon: starch: LiBF4 and lithium carbonate of 40:30:10:10, add the weighed materials into the ethanol solvent, and stir with a magnetic stirrer for 3 hours. Ensure that the nano-silicon, starch, LiBF4 and lithium carbonate are fully dispersed in the solvent to avoid agglomeration.
[0036] Step 2: The suspension obtained in step 1 is treated by extrusion granulation, and the inlet temperature of the extruder is controlled to be 150°C and the outlet temperature is controlled to be 80°C: the inlet temperature of the extruder is set to 150°C, the outlet temperature is set to 80°C, the suspension obtained in step 1 is injected into the extruder, the extruder is turned on, the extrusion speed is adjusted, and the sample after pressurized granulation is obtained.
[0037] Step 3: The pressurized granulated sample obtained in step 2 is calcined twice under an inert atmosphere to obtain a silicon-carbon negative electrode precursor material: After the furnace is preheated, the pressurized granulated sample obtained in step 2 is placed in a furnace and calcined under an inert atmosphere. The calcination temperature is between 850°C, the heating rate is controlled at 5°C / min, and the insulation time is 2 hours, so that the sample undergoes a chemical reaction at high temperature. After the calcination is completed, the sample is taken out of the furnace, and the sample after the first calcination is placed in a high-temperature resistant container again. Similarly, ensure that the container is sealed under an inert atmosphere, put the container into a high-temperature furnace, and raise the temperature to 1100°C at 5°C / min. The insulation time is 2 hours. After the calcination is completed, the high-temperature furnace is turned off, and the sample is naturally cooled to room temperature. The sample is taken out to obtain a silicon-carbon negative electrode precursor material.
[0038] Step 4: Using chemical vapor deposition, at a temperature of 850° C., use a mixed gas of acetylene and methane to perform carbon coating treatment on the silicon-carbon negative electrode precursor material obtained in step 3 for 1 hour to obtain a carbon-coated negative electrode material.
[0039] Step 5. After the carbon-coated negative electrode material obtained in step 4 is fully dried, it is mixed with polyvinylidene fluoride in a mass ratio of 9.9:0.1, and placed in a mixing container for mechanical stirring to make the two mixed evenly, and then the material is pre-pressed. The pre-pressed green body is placed in a heat treatment furnace, heated at a rate of 10°C / min, and heat treated at 750°C. After the heat treatment, the power is turned off, and the heat-treated green body is naturally cooled to room temperature in the furnace, taken out, and the burrs are removed to obtain the desired silicon-carbon negative electrode material.
[0040] Comparative Example 3
[0041] Step 1: Weigh the raw materials according to the mass ratio of nano silicon: starch: LiBF4 and lithium carbonate of 40:40:10:10, add the weighed materials into ethanol solvent, and stir with a magnetic stirrer for 3 hours. Ensure that the nano silicon, starch, LiBF4 and lithium carbonate are fully dispersed in the solvent to avoid agglomeration.
[0042] Step 2: Set the inlet temperature of the extruder to 150°C and the outlet temperature to 80°C, inject the suspension obtained in step 1 into the extruder, start the extruder, adjust the extrusion speed, and obtain a sample after pressurized granulation.
[0043] Step 3: After the furnace is preheated, the pressurized granulated sample obtained in step 2 is placed in the furnace and calcined under an inert atmosphere. The calcination temperature is between 850°C, the heating rate is controlled at 5°C / min, and the insulation time is 2 hours. The sample is allowed to undergo a chemical reaction at high temperature. After the calcination is completed, the sample is taken out of the furnace, naturally cooled to room temperature, and the sample is taken out to obtain a silicon-carbon negative electrode precursor material.
[0044] Step 4: Using chemical vapor deposition, at a temperature of 850° C., use a mixed gas of acetylene and methane to perform carbon coating treatment on the silicon-carbon negative electrode precursor material obtained in step 3 for 1 hour to obtain a carbon-coated negative electrode material.
[0045] Step 5. After the carbon-coated negative electrode material obtained in step 4 is fully dried, it is mixed with polyvinylidene fluoride in a mass ratio of 9.9:0.1, and placed in a mixing container for mechanical stirring to make the two mixed evenly, and then the material is pre-pressed. The pre-pressed green body is placed in a heat treatment furnace, heated at a rate of 10°C / min, and heat treated at 750°C. After the heat treatment, the power is turned off, and the heat-treated green body is naturally cooled to room temperature in the furnace, taken out, and the burrs are removed to obtain the desired silicon-carbon negative electrode material.
[0046] Comparative Example 4
[0047] Step 1: Disperse nano-silicon, carbon source, LiBF4 and lithium carbonate in a solvent and stir to obtain a suspension: weigh the raw materials according to the mass ratio of nano-silicon: starch: LiBF4 and lithium carbonate of 40:40:10:10, add the weighed materials into the ethanol solvent, and stir with a magnetic stirrer for 3 hours. Ensure that the nano-silicon, starch, LiBF4 and lithium carbonate are fully dispersed in the solvent to avoid agglomeration.
[0048] Step 2: The suspension obtained in step 1 is treated by extrusion granulation, and the inlet temperature of the extruder is controlled to be 150°C and the outlet temperature is controlled to be 80°C: the inlet temperature of the extruder is set to 150°C, the outlet temperature is set to 80°C, the suspension obtained in step 1 is injected into the extruder, the extruder is turned on, the extrusion speed is adjusted, and the sample after pressurized granulation is obtained.
[0049] Step 3: Calcine the pressurized granulated sample obtained in step 2 twice under an inert atmosphere to obtain a silicon-carbon negative electrode precursor material: After the furnace is preheated, the pressurized granulated sample obtained in step 2 is placed in a furnace and calcined under an inert atmosphere. The calcination temperature is between 850°C, the heating rate is controlled at 5°C / min, and the insulation time is 2 hours. The sample undergoes a chemical reaction at high temperature. After the calcination is completed, the sample is taken out of the furnace and naturally cooled to room temperature to obtain a silicon-carbon negative electrode precursor material.
[0050] Step 4: Using chemical vapor deposition, at a temperature of 850° C., use a mixed gas of acetylene and methane to perform carbon coating treatment on the silicon-carbon negative electrode precursor material obtained in step 3 for 1 hour to obtain a carbon-coated negative electrode material.
[0051] Step 5. After the carbon-coated negative electrode material obtained in step 4 is fully dried, it is mixed with polyvinylidene fluoride in a mass ratio of 9.9:0.1, and placed in a mixing container for mechanical stirring to make the two mixed evenly, and then the material is pre-pressed. The pre-pressed green body is placed in a heat treatment furnace, heated at a rate of 10°C / min, and heat treated at 750°C. After the heat treatment, the power is turned off, and the heat-treated green body is naturally cooled to room temperature in the furnace, taken out, and the burrs are removed to obtain the desired silicon-carbon negative electrode material.
[0052] Comparative Example 5
[0053] Step 1: Weigh the raw materials according to the mass ratio of nano-silicon: carbon source: LiBF4, lithium carbonate of 40:40:10:10, add the weighed materials into ethanol solvent, and stir with a magnetic stirrer for 3 hours. Ensure that nano-silicon, starch, LiBF4 and lithium carbonate are fully dispersed in the solvent to avoid agglomeration.
[0054] Step 2, the suspension obtained in step 1 is treated by extrusion granulation, and the inlet temperature of the extruder is controlled to be 150°C and the outlet temperature is controlled to be 80°C: the inlet temperature of the extruder is set to 150°C, the outlet temperature is set to 80°C, the suspension obtained in step 1 is injected into the extruder, the extruder is turned on, the extrusion speed is adjusted, and the sample after pressurized granulation is obtained.
[0055] Step 3, the pressurized granulated sample obtained in step 2 is calcined twice under an inert atmosphere to obtain a silicon-carbon negative electrode precursor material: after the furnace is preheated, the pressurized granulated sample obtained in step 2 is placed in a furnace and calcined in an inert atmosphere, the calcination temperature is between 850°C, the heating rate is controlled at 5°C / min, and the insulation time is 2 hours, so that the sample undergoes a chemical reaction at high temperature. After the calcination is completed, the sample is taken out of the furnace, and the sample after the first calcination is placed in a high temperature resistant container again, and the container is also ensured to be sealed under an inert atmosphere. The container is placed in a high temperature furnace, and the temperature is raised to 1100°C at 5°C / min, and the insulation time is 2 hours. After the calcination is completed, the high temperature furnace is turned off, and it is naturally cooled to room temperature. The sample is taken out to obtain a silicon-carbon negative electrode precursor material.
[0056] Step 4. After the silicon-carbon negative electrode precursor material obtained in step 3 is fully dried, it is mixed with polyvinylidene fluoride in a mass ratio of 9.9:0.1, and placed in a mixing container for mechanical stirring to make the two mixed evenly, and then the material is pre-pressed. The pre-pressed body is placed in a heat treatment furnace, heated at a rate of 10°C / min, and heat treated at 750°C. After the heat treatment, the power is turned off, and the heat-treated body is naturally cooled to room temperature in the furnace, taken out, and the burrs are removed to obtain the desired silicon-carbon negative electrode material.
[0057] Comparative Example 6
[0058] Step 1: Weigh the raw materials according to the mass ratio of nano-silicon: carbon source: LiBF4, lithium carbonate of 40:40:10:10, add the weighed materials into ethanol solvent, and stir with a magnetic stirrer for 3 hours. Ensure that the nano-silicon, starch, LiBF4 and lithium carbonate are fully dispersed in the solvent to avoid agglomeration.
[0059] Step 2, the suspension obtained in step 1 is treated by extrusion granulation, and the inlet temperature of the extruder is controlled to be 150°C and the outlet temperature is controlled to be 80°C: the inlet temperature of the extruder is set to 150°C, the outlet temperature is set to 80°C, the suspension obtained in step 1 is injected into the extruder, the extruder is turned on, the extrusion speed is adjusted, and the sample after pressurized granulation is obtained.
[0060] Step 3, the pressurized granulated sample obtained in step 2 is calcined twice under an inert atmosphere to obtain a silicon-carbon negative electrode precursor material: after the furnace is preheated, the pressurized granulated sample obtained in step 2 is placed in a furnace and calcined in an inert atmosphere, the calcination temperature is between 850°C, the heating rate is controlled at 5°C / min, and the insulation time is 2 hours, so that the sample undergoes a chemical reaction at high temperature. After the calcination is completed, the sample is taken out of the furnace, and the sample after the first calcination is placed in a high temperature resistant container again, and the container is also ensured to be sealed under an inert atmosphere. The container is placed in a high temperature furnace, and the temperature is raised to 1100°C at 5°C / min, and the insulation time is 2 hours. After the calcination is completed, the high temperature furnace is turned off, and it is naturally cooled to room temperature. The sample is taken out to obtain a silicon-carbon negative electrode precursor material.
[0061] Step 4: using a chemical vapor deposition method, at a temperature of 850° C., using a mixed gas of acetylene and methane to perform a carbon coating treatment on the silicon-carbon negative electrode precursor material obtained in step 3 for 1 hour to obtain a carbon-coated silicon-carbon negative electrode material;
[0062] The silicon-carbon negative electrode material obtained in Example 1 and Comparative Examples 1-6, the conductive carbon black SP, CMC, and SBR were stirred vigorously in deionized water at a mass ratio of 90:2:2:4 to prepare a uniformly mixed slurry, and then the slurry was evenly coated on the copper foil current collector, baked in an oven at 80°C for 10 hours, and cut into circular pole pieces with a diameter of 10 mm. A metal lithium sheet was used as the positive electrode, a PP / PE / PP microporous membrane (Celgard2400) was used as the separator, and 1.15 mol / LLiPF6 (the solvent was a mixed solution of ethylene carbonate, dimethyl carbonate, and diethyl carbonate in a volume ratio of 1:1:1) was used as the electrolyte. A button cell was assembled in an argon-protected glove box, and a charge and discharge test was performed. The results are shown in Table 1.
[0063] Table 1 Constant current charge and discharge test results
[0064]
[0065]
[0066] Therefore, the present application provides a silicon-carbon negative electrode material with high mechanical strength, which solves the technical problem that the porous silicon-carbon negative electrode material in the prior art has low loose density and compacted density, which is not conducive to the preparation of high-surface-load battery electrodes and limits the energy density of the battery.
[0067] In the description of this specification, the description with reference to the terms "an experimental example", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the experimental example or example are included in at least one experimental example or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same experimental example or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more experimental examples or examples in a suitable manner.
[0068] Finally, it should be noted that the above experimental examples are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred experimental examples, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A silicon-carbon negative electrode material with high mechanical strength, characterized in that: The method comprises the following preparation steps: Step 1, dispersing nano-silicon, carbon source, LiBF4 and lithium carbonate in a solvent, and stirring to obtain a suspension; Step 2, the suspension obtained in step 1 is treated by extrusion granulation to obtain a sample after pressurized granulation, and the inlet temperature of the extruder is controlled to be 150° C. and the outlet temperature is controlled to be 80° C.; Step 3, calcining the pressurized granulated sample obtained in step 2 twice under an inert atmosphere to obtain a silicon-carbon negative electrode precursor material; Step 4, subjecting the silicon-carbon negative electrode precursor material obtained in step 3 to carbon coating treatment by chemical vapor deposition to obtain a carbon-coated negative electrode material; Step 5: Compound the carbon-coated negative electrode material obtained in step 4 with PVDF in a mass ratio of 9.9:0.1, and perform heat treatment at 750° C. to obtain the desired silicon-carbon negative electrode material.
2. The silicon-carbon negative electrode material with high mechanical strength according to claim 1, characterized in that: In the step 1, the mass ratio of nano-silicon: carbon source: LiBF4: lithium carbonate is 40:40:10:
10.
3. The silicon-carbon negative electrode material with high mechanical strength according to claim 1, characterized in that: In step 3, the first calcination temperature is 850°C, the heating rate is controlled at 5°C / min, and the insulation time is 2 hours; the second calcination temperature is 1100°C, the heating rate is controlled at 5°C / min, and the insulation time is 2 hours.
4. The silicon-carbon negative electrode material with high mechanical strength according to claim 1, characterized in that: In the step 1, nano-silicon, carbon source, LiBF4 and lithium carbonate are dispersed in a solvent and stirred using a magnetic stirrer for 1-3 hours.
5. The silicon-carbon negative electrode material with high mechanical strength according to claim 1, characterized in that: In step 1, the carbon source is one or more of starch, citric acid, phenolic resin, asphalt and polyvinyl pyrrolidone.
6. The silicon-carbon negative electrode material with high mechanical strength according to claim 1, characterized in that: In step 1, the solvent is one or more of ethanol and isopropanol.
7. The silicon-carbon negative electrode material with high mechanical strength according to claim 1, characterized in that: In step 1, the carbon source further comprises one or more of graphite, carbon fiber and graphene oxide.
8. The silicon-carbon negative electrode material with high mechanical strength according to claim 1, characterized in that: In step 4, the temperature of carbon coating is 850° C., the gas source used is a mixed gas of acetylene and methane, and the duration is 1 hour.
Citation Information
Cited By
Silicon-based negative electrode material for all-solid-state battery as well as preparation method and application of silicon-based negative electrode material
CN119627087A
